PEMAKAIAN KATA BAHASA INGGRIS DALAM OLAHRAGA BULUTANGKIS DI MA AL IRSYAD GAJAH DEMAK JAWA TENGAH (SUATU PENDEKATAN SOSIOLINGUISTIK) - Ulya Himawati (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2018)
This article describes the characteristics of language usage in badminton sport at MA AlIrsyad Gajah Demak. The use of language in badminton also has its own characteristic thatis different from the term on other sports. The use of language in badminton a lot of influencefrom the English language. Therefore, research on the use of language in badminton needs tobe done to solve linguistic problems in this sport. In this study used the method of presentingthe results of data analysis informally. The method of informal presentation is theformulation with ordinary words even with technical terminology. The method used is theresult of data analysis will materialize the explanation that is related to the characteristics oflanguage usage, language function in badminton sport, and special vocabulary in badmintonsport. Explanation will description tangible sentences followed by giving meaning in detail.Keywords: English language usage, Sociolinguistic, badminton sport